Knowledge and associated factors with respect to prevention of post-traumatic compartment syndrome among surgical unit nurses; a multi-center cross-sectional study - Astewil Moges Bazezew; Yalemwork Getahun; Tiruye Azene Demlie; Desalegn Getachew Ayele; Tsehayu Melak Siyoum; Gezahagn Demsu Gedefaw; Kasaye Ahmed Zeleke; Esayas Alemshet Tekletsadik; Sintayehu Simie Tsega; Melkamu Tilahun Dessie; Ashenafi Fekad Getahun; Ashenafi Worku Woretaw (BMC, 2024)
Abstract Background Delayed recognition of compartment syndrome can result in devastating consequences such as the need for amputation or even death. Nurses are at the frontline of patient care and they must have a high index of suspicion for compartment syndrome. Even though nurses' knowledge about the prevention of compartment syndrome is important, there are no studies in Ethiopia. Therefore this study aims to assess the knowledge and associated factors of nurses towards the prevention of post-traumatic compartment syndrome. Method An institutional-based cross-sectional study was conducted among 410 nurses from 26 April to 25 May 2023 at five Comprehensive Specialized Hospital. A stratified sampling technique was employed to recruit the required participants for the study. The data were collected using a structured self-administered questionnaire. The descriptive statistics were presented in text and tables. Analytical analysis schemes including bivariable and multivariable logistic regression were computed considering P-value < 0.05 to identify statistically significant factors. Result Nearly three- fifths (61.6%; 95% CI: 56.7 to 66.3) of nurses had adequate knowledge and significantly associated with being male (AOR: 1.615, 95% CI: 1.050-2.485), nurse use of guidelines (AOR: 2.079, 95% CI: 1.307-3.307), nurses they have been trained (AOR = 1.650; 95 CI: 1.063-2.562), and nurses' who had more than 15 years' (AOR: 4.207, 95 CI: 1.762-10.045) experience had good knowledge with respect to prevention of compartment syndrome than the counterparts. Conclusion Even though nurses' knowledge regarding the prevention of post-traumatic compartment syndrome was found to be good, Diligent nursing assessment and monitoring of clinical signs should be critically performed. So, it is better to strengthen training, equip wards with standardized guidelines, and create a safe working environment should be routine activities.